Squeegees

Calculus Level 3

An infinitely thin, k cm k\text{ cm} -long squeegee begins to slide down from the upper-left corner of a k cm × k cm k\text{ cm} \times k\text{ cm} square window. Its other end simultaneously slides toward the lower-right corner of the window, with the upper end kept in contact with the left side of the window.

If k = 2016 π k=\sqrt{\dfrac{2016}{\pi }} , what is the area of the window ( \big( in cm 2 ) \text{cm}^2\big) cleaned by the squeegee?

Note : you may end up with an integral expression that's difficult to evaluate analytically. Feel free to finish the job using the code environment below:

import math
Python 3
You need to be connected to run code


The answer is 189.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Miles Koumouris
Oct 15, 2017

Sorry for the inconsistent image size; it would have been tiresome to copy and edit the TeX into the solutions box.

How did you figure out the first equation ?

Alessandro Mattia - 3 years, 7 months ago

Log in to reply

Consider the right-angled triangle formed by the squeegee and the two perpendicular sides of the window; if the squeegee has length k k , and its right end is at some distance n n from the left corner, then by Pythagoras's theorem, the left side of the triangle is given by k 2 n 2 \sqrt{k^2-n^2} . Then the gradient of the squeegee is k 2 n 2 n \dfrac{-\sqrt{k^2-n^2}}{n} . The y y intercept is also just the left side of the triangle, which is k 2 n 2 \sqrt{k^2-n^2} , so the equation of squeegee becomes S ( x ) = k 2 n 2 n x + k 2 n 2 S(x)=\dfrac{-\sqrt{k^2-n^2}}{n}x+\sqrt{k^2-n^2} .

Miles Koumouris - 3 years, 6 months ago

Log in to reply

Got it! thanks!

Alessandro Mattia - 3 years, 6 months ago
Pedro Cardoso
Oct 20, 2017

Placing the window in the cartesian plane, with the bottom left corner ar (0,0), at any given time, the squeegee makes an angle θ \theta with the horizontal, that goes from π 2 \frac{\pi}{2} to 0 0 , If you consider a new sqeegee at angle θ = θ + h \theta'=\theta+h , the two squeegees intersect at a point P P' . As h 0 h\rightarrow 0 , P P P'\rightarrow P , and P P depends on θ \theta . All these limit intersection points are, of course, points in the edge of the area swept by the sqeegee, and vice-versa. This is the main statement on which this solution is based. *For simplicity, I considered a sqeegee of length 1 1 , we'll just have to remember to multiply the area by k 2 k^2 in the end to get the correct answer. Since the squeegee has length 1 1 , from triangle O A B \triangle OAB , we see that A O = sin θ \overline { AO }=\sin { \theta } , B O = cos θ \overline { BO }=\cos { \theta } , and consequently, A A = cos θ d θ \overline { AA' } =\cos { \theta } d\theta , and B B = sin θ d θ \overline { BB' } =\sin { \theta } d\theta . Now, from triangles D A A \triangle DAA' and O A B \triangle OA'B' , we see that A D ^ A = A B ^ O \angle A\widehat { D } A'=\angle A'\widehat { B' } O , so D A = A A cot θ \overline { DA } =\overline { A'A } \cot { \theta } which means D A = cos 2 θ sin θ d θ \large \overline { DA } =\frac { \cos ^{ 2 }{ \theta } }{ \sin { \theta } } d\theta . Finally, from similar triangles D A P \triangle DAP and P B B \triangle PBB' , D A A P = B B P B \large \frac { \overline { DA } }{ \overline { AP } } =\frac { \overline { BB' } }{ \overline { PB' } } , but we know that A P + P B = 1 \overline { AP } +\overline { PB } =1 . Then, making P B = p \overline { PB } =p and substituting what we found earlier, we have cos 2 θ ( p 1 ) sin θ = sin θ p \frac{\cos^2\theta}{\left(p-1\right)\sin\theta}=\frac{\sin\theta}{p} p = ( 1 p ) tan 2 θ p=\left(1-p\right)\tan^2\theta p = tan 2 θ ( 1 + tan 2 θ ) p=\frac{\tan^2\theta}{\left(1+\tan^2\theta\right)} p = sin 2 θ p=\sin^2\theta Then, the coordinates of the point P P with respect to θ \theta are x ( θ ) = cos θ ( cos θ ) sin 2 θ x\left(\theta\right)=\cos\theta-\left(\cos\theta\right)\sin^2\theta y ( θ ) = ( sin θ ) sin 2 θ y\left(\theta\right)=\left(\sin\theta\right)\sin^2\theta Simplifying, we have x ( θ ) = cos 3 θ x\left(\theta\right)=\cos^3\theta y ( θ ) = sin 3 θ y\left(\theta\right)=\sin^3\theta Finally, we know that the area under a parametric curve is t 1 t 2 y ( t ) x ( t ) d t \large \int_{t_1}^{t_2}y\left(t\right)x'\left(t\right)dt , so substituting for wat we have, and multiplying by k 2 k^2 : A r e a = 2016 π 0 π 2 3 sin 4 ( t ) cos 2 ( t ) d t = 189 \large Area=\frac{2016}{\pi}\int_0^{\frac{\pi}{2}}3\sin^4\left(t\right)\cos^2\left(t\right)dt=189

Could you please explain what AA' = sin theta d there? Thanks!

Mohannad Elhamod - 3 years, 7 months ago

Log in to reply

Thanks for ponting this out! I'll fix it. I actually mistakenly switched the expressions for AA' and BB', I only did it right there at the beginning, so the rest of the solution is correct. Here's the correct reasoning:

Say the height of the point where the sqeegee touches the y axis is h h which is, of course equal to sin θ \sin { \theta } , well, d h d θ = cos θ \frac { dh }{ d\theta } =\cos { \theta } , so d h = cos θ d θ dh=\cos { \theta } d\theta , which is the same thing as AA': A tiny change in height caused by a tiny change in θ \theta . The reasoning for BB' is analogous.

Pedro Cardoso - 3 years, 7 months ago

Why are you not able to simply solve this by creating a larger square made up from 4 of the ones shown\ then getting the area of the internal circle, subtracting it from the area of the larger square and divide by 4? is the blue area shown not a quarter circle?

Matt Balisky - 3 years, 7 months ago

Log in to reply

The blue area is actually not a quarter circle its slightly bigger than that

Pedro Cardoso - 3 years, 7 months ago
Shaun Leong
Oct 16, 2017

Let the square be represented in Cartesian coordinates, with ( 0 , 0 ) (0,0) as the bottom left corner and ( 0 , k ) (0,k) as the top left corner.

At any time, let ϕ \phi be the angle between the squeegee and the vertical. Initially ϕ = 0 \phi=0 and at the end ϕ = π 2 \phi=\dfrac{\pi}{2} .

The squeegee forms a line with gradient cot ϕ -\cot{\phi} and y-intercept k cos ϕ k\cos{\phi} . Thus it has the equation y = k cos ϕ cot ϕ x y=k\cos{\phi}-\cot{\phi}x

A point is considered cleaned if it has been on a squeegee before. In other words, an angle ϕ \phi must exist such that 0 ϕ π 2 0 \leq \phi \leq \dfrac{\pi}{2} which satisfies [y=k\cos{\phi}-\cot{\phi} x]

If we fix x x then there will be a range of y y values. The curve is given by the maximum y-values. Differentiating y y with respect to p h i phi , d y d ϕ = k sin ϕ + csc 2 ϕ x \dfrac{dy}{d\phi}=-k\sin{\phi}+\csc^2 {\phi}x

The ϕ \phi yielding the y m a x y_{max} is given by sin ϕ = x k 3 \sin{\phi}=\sqrt[3]{\dfrac{x}{k}} y m a x = k ( 1 ( x k ) 2 3 ) 3 2 \Rightarrow y_{max}=k\left(1-\left(\dfrac{x}{k}\right)^{\frac23}\right)^{\frac32}

Integrating, the cleaned area is

k 0 k ( 1 ( x k ) 2 3 ) 3 2 d x k\int^k_0 \left(1-\left(\dfrac{x}{k}\right)^{\frac23}\right)^{\frac32}dx

Let r = x k d x = k d r r=\dfrac{x}{k} \Rightarrow dx=k dr = k 2 0 1 ( 1 r 2 3 ) 3 2 d r =k^2\int^1_0 \left(1-r^{\frac23}\right)^{\frac32}dr

Let r = sin 3 θ 3 sin 2 θ cos θ r=\sin^3 {\theta} \Rightarrow 3\sin^2 {\theta}\cos{\theta} = 3 k 2 2 0 π 2 2 sin 2 θ cos 4 θ d θ =\dfrac{3k^2}{2}\int^\frac{\pi}{2}_0 2\sin^2{\theta}\cos^4{\theta}d\theta = 3 k 2 2 Γ ( 5 2 ) + Γ ( 3 2 ) Γ ( 5 2 + 3 2 ) =\dfrac{3k^2}{2}\dfrac{\Gamma(\frac52)+\Gamma(\frac32)}{\Gamma(\frac52+\frac32)} = 3 2 ( 2016 π ) ( 3 2 ) ( 1 2 ) 2 ( π ) 2 6 =\dfrac32\left(\dfrac{2016}{\pi}\right)\dfrac{\left(\dfrac32\right)\left(\dfrac12\right)^2(\sqrt{\pi})^2}{6} = 189 =\boxed{189}

Each line ha the form

F ( t , x , y ) = k sin ( t ) + x tan ( t ) + y = 0 F(t,x,y)=-k \sin (t)+x \tan (t)+y=0

for 0 < = t < = π / 2 0<=t<=\pi/2 .

Equation of the envelope is all (x,y) such that

F ( t , x , y ) = 0 , F ( 1 , 0 , 0 ) ( t , x , y ) = 0 F(t,x,y) = 0, F^{(1,0,0)}(t,x,y) = 0

Solving for x,y we get

{ x = k cos 3 ( t ) , y = k sin ( t ) k sin ( t ) cos 2 ( t ) } \left\{x=k \cos ^3(t),y=k \sin (t)-k \sin (t) \cos ^2(t)\right\}

So we want

π 2 0 y ( x ( t ) ) x ( t ) d t = 3 π k 2 32 \int_{\frac{\pi }{2}}^0 y(x(t)) x'(t) \, dt = \frac{3 \pi k^2}{32}

which gives 189 with k above.

Yuriy Kazakov
Oct 25, 2017

I use formula for astroid area. http://www.wolframalpha.com/input/?i=astroid

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...